2018
DOI: 10.1136/bcr-2018-224361
|View full text |Cite
|
Sign up to set email alerts
|

Unusual case of simple urinary bladder melanosis with complete resolution

Abstract: A 66-year-old man presented with a long history of recurrent attacks of urinary retention and lower urinary tract symptoms. Flexible cystoscopy showed a urethral stricture. Follow-up cystoscopy 7 years later for recurrent symptoms demonstrated unusual extensive mucosal brown to black pigmentation, which proved histopathologically to be a simple bladder melanosis. Follow-up demonstrated complete resolution over a period of 1 year with no specific treatment. In this report, we highlighted a rare bladder abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…On the contrary, Mera et al reported on a patient followed endoscopically 1 year after his diagnosis of bladder melanosis who had complete resolution of the melanosis without any specific treatment. 21 It has been suggested that these patients undergo annual surveillance cystoscopy due to the level of uncertainty that surrounds this diagnosis. 22,23 The longest reported follow-up in the literature is 10 years during which time the patient had repeated cystoscopy and biopsy, however, this patient subsequently proceeded to benign cystectomy due to refractory lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Mera et al reported on a patient followed endoscopically 1 year after his diagnosis of bladder melanosis who had complete resolution of the melanosis without any specific treatment. 21 It has been suggested that these patients undergo annual surveillance cystoscopy due to the level of uncertainty that surrounds this diagnosis. 22,23 The longest reported follow-up in the literature is 10 years during which time the patient had repeated cystoscopy and biopsy, however, this patient subsequently proceeded to benign cystectomy due to refractory lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder melanosis has been reported in patients with a variety of symptoms and findings, including: urinary obstruction, urgency, and incontinence; lower urinary tract symptoms; flank or loin pain; haematuria; and UTIs. It may be a transient phenomenon: one report [ 19 ] indicates that melanosis may completely resolve spontaneously within a year. It has also resolved after BCG therapy for urothelial carcinoma [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through a thorough review of the literature we identified 30 cases of “melanosis” of the bladder, occurring in 17 men and 13 women, aged 43 to 86 (mean 65) years. The patients presented with lower urinary tract symptoms, gross hematuria or flank pain, and showed punctate, patchy or diffuse brown‐black discoloration of the bladder mucosa on cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The urine cytologic findings in previously reported cases were poorly documented; they were not mentioned at all in 15 cases, 10,12,15,17,[20][21][22]29,30,34 were reported as "negative" or "unremarkable" in eight cases, 14,16,18,19,24,26,32,33 and "atypical" in a single case. 31 In the remaining five cases, the cells containing pigment were seen.…”
Section: Discussionmentioning
confidence: 99%